Obesity and Gut Microbiota: a Succinct Evaluation - Anujem, Evidence; Anujem, Salvation (International Journal on Food, Agriculture and Natural Resources, 2025)
Obesity has been of global health concern, contributing to a wide range of chronic diseases such as cardiovascular disease, type 2 diabetes, and certain cancers. Recent research has illuminated the complex role of gut microbiota in the development and progression of obesity The gut microbiota tempers host metabolism through mechanisms like fermentation of dietary fibers, production of short-chain fatty acids, and regulation of appetite-related hormones. Addressing obesity through a microbiota-centric approach necessitates comprehensive strategies that integrate dietary modifications, lifestyle intervention and consideration of culture. The gut microbiota affects metabolism and immune function which are crucial for energy regulation and fat storage. This review examines the interplay between obesity and dysbiosis, emphasizing the critical roles of diet and lifestyle as understanding these dynamics informs tailored interventions for obesity prevention and management.